OCT ANGIOGRAPHY (OCTA) - Jabbari, Aidila Jesmin (International Journal of Allied Health Sciences, 2021)
OCT Angiography(OCTA) allows us to visualize the retinal and choroidal structures as well the blood flow. It is a fast, non invasive imaging system. As such it has multiple uses in terms of research, diagnosis and monitoring of patients. OCTA allows for early detection of macula ischaemia in the presence of good vision. This would otherwise be missed even with the OCT.